Analysis of gene expression profiles in melanoma cells with acquired resistance against antineoplastic drugs - Gyorffy, Balazs; Schadendorf, Dirk (Melanoma research, 2006)
Resistance to various antineoplastic agents is common in the clinical management of malignant melanoma. The biological mechanisms conferring these different drug-resistant phenotypes are still unclear. To identify potential factors mediating drug resistance to melanoma cells, the mRNA expression profiles of the parental drug-sensitive human melanoma cell line MeWo and four derived drug-resistant sublines with acquired resistance against four commonly used drugs for melanoma treatment (cisplatin, etoposide, fotemustine and vindesine) were analysed. We investigated cDNA arrays with 43 000 cDNA clones (∼30 000 unique genes) to study the expression patterns of these cell lines. We were able to simultaneously extract new candidate genes associated with drug resistance in malignant melanoma and to correlate the present findings with previously described resistance-associated genes. Using hierarchical clustering and analysing the overlap of genes with altered expression, we detected similarities between the expression signatures related to cisplatin and fotemustine resistance. The resistance against vindesine required a minimal set of changes in gene expression relative to the parental MeWo cell line. Our study provides new data that may be used to obtain further insight into the resistance characteristics of malignant melanoma.
Gesehen am 11.02.2021